Professionally Yours: Anonymity, Trust, and Self-Portrayal on the Deep Web - Jakaitis, Leah Berkman; Abdul-Mageed, Muhammad (AoIR Selected Papers of Internet Research, 2013)
The deep web (DW) is the collective data, forums, and websites on the unindexed internet. The DW provides an online environment that allows users to participate in illicit transactions with greater security and anonymity than that available on the surface web. Multiple DW marketplaces have been established, specializing in black market wares – ranging from drugs and weapons to pornography and forged documents. DW traffickers work to create a reliable, trustworthy persona to establish credibility, and present a professional veneer for engaging with potential and current customers. In this paper, we investigate the mechanisms of anonymity, trust, and traffickers’ self-portrayal as reputable and reliable businesspeople on the DW. We show that even though DW traffickers partake in illegal activities, both the trust mechanisms and the strategies deployed for the establishment of seller reputations on the DW are, with a few nuances, similar to those adopted on the ‘surface-web’ marketplaces.